Теоретичне обґрунтування феномену іміджу - Остапйовський, Ігор Євгенович; Остапйовська, Тетяна; Ostapyovsky, Ihor; Ostapyovska, Tatiana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розкрито актуальність проблеми дослідження, здійснено її теоретичний аналіз, власне визначення іміджу. Для пояснення теоретичних засад феномену іміджу розроблено структурно-функціональну модель, яка представлена методологічним, змістово-процесуальним та діагностико-корекційним компонентами. В статье раскрыта актуальность проблемы исследования. Осуществлен ее теоретический анализ. Дано собственное определение имиджа. Установлено, что имидж – это целенаправленно сформированный стереотипизированной образ определенного объекта, который существует в массовом сознании. Для объяснения теоретических основ феномена имиджа разработана структурно-функциональная модель. Предложенная модель представлена методологическим, содержательно-процессуальным и диагностико-коррекционным компонентами. Методологический компонент включает законы, принципы, методологические подходы. Содержательно-процессуальный – типы имиджа, внешние и внутренние факторы его формирования, технологии, функции. Диагностика и коррекция автомониторинга личности – составная диагностико-коррекционного компонента.The urgency of the substantiation is discovered in the article. Its theoretical analysis is carried. Own definition of image is given. It was found that the image is purposefully formed stereotyped appearance of a particular object that exists in the public mind. To explain the theoretical foundations of the phenomenon of image developed structural-functional model. The proposed model is presented methodological, substantive and procedural and diagnostic and corrective components. Methodological component includes laws, principles, methodological approaches. Substantive and procedural component of image are types, external and internal factors of its formation, technologies and functions. Diagnostics and correction self-monitoring personality is an integral component of the diagnostic and corrective.
Theoretical Substantiation of the Phenomenon of Image.
Keywords: імідж, типи іміджу, функції іміджу, закони, принципи, структурно-функціональна модель.; имидж, типы имиджа, функции имиджа, законы, принципы, структурно-функциональная модель.; image, image type, image functions, laws, principles, structural-functional model.